Blue Ocean Strategy to Develop School Competitiveness: A Case Study - Octavira, Ira Nadya; Permana, Johar; Prihatin, Eka; Hartini, Nani; Muamar, M. Rezeki (Indonesian Research Journal in Education |IRJE|, 2024)
The large number of educational units organized by the government or the community has resulted in intense competition in recruiting students. This research aims to implement the Blue Ocean strategy at SMP Pelita YPH Sukabumi to win the competition with other secondary schools in Sukabumi. This qualitative research consists of three stages: SWOT analysis, canvas strategy, and four-action frameworks for developing a Blue Ocean strategy. Furthermore, the results showed that to create a new market for SMP Pelita YNH Sukabumi through a Blue Ocean strategy, SMP Pelita YNH Sukabumi needs to (1) eliminate education costs, (2) increase the quality and quantity of teaching staff, facilities and infrastructures, and promotion, (3) reduce the variety of extracurricular activities and focusing on extracurricular in culinary activities, and (4) creating culinary classes and school business units.